Mine d’or et développement durable - Mouhamadou Lamine Diallo (EchoGéo)
The revival of mining activities in western Senegal began with Sabodala mining project. Similarly to its region (Tambacounda), Sabodala is a remote village where traditional activities such as agriculture and gold digging are mainly practised. Poverty is perceived through joblessness among young people, the absence of social and economical infrastructures and the lack of thoroughfare. Therefore, the setting up of a new mining industry gives rise to hope within villagers and specially the government along with the allocated companies namely Mineral Deposits Limited (Mineral Deposit Limited - MDL), that are claiming sustainable development principles. However the gap between these demands and the results in the field induces to wonder whether it’s possible to establish a linkage between mining project and development at the local scale.